Sosialisasi Pemberdayaan Situs Geologi untuk Pengembangan Wisata Desa Purwodadi, Malang - Susilo, Adi; Pamungkas, Mauludi Ariesto; Juwono, Alamsyah M.; Naba, Agus; Yudianto, Didik; Hasan, Muhammad Fathur Rouf (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Purwodadi Village is located in the southern part of Malang Regency with a karst area which presents a beautiful panorama of rock outcrops and forms a collection of geological sites, so this area has the potential to be developed as a geotourism. Optimizing the use of geological sites and digital technology in the tourism sector will bring extraordinary benefits. This service activity aims to socialize the empowerment of geological sites to support Purwodadi Tourism Village as a geotourism centre. This activity is in collaboration with the Purwodadi Village-Owned Enterprise "Dadi Mulyo" and the Purwodadi Village Government, who also participate in the activity. The socialization is carried out to provide an overview and demonstration of the empowerment of geological sites as well as efforts that can be made to introduce geological sites to the wider community, such as digitization through the website. While the geological survey aims to map the variety of geological sites owned by Purwodadi Village, which have the potential to attract visitors. The final target of this activity is to increase the number of tourist visitors in the hope of increasing income generating BUMDes and the local government.